Evaluasi Implementasi Program Bantuan Pendidikan Di Indonesia: Analisis Efektivitas PIP, KIP Kuliah, Dan BOS Melalui Studi Literatur - Priska Adelia Putri; Zara Handayani; Renanda Rakista; Dinda Yuvia Ibnayasha; Ibdia Zikra; Jumiati Jumiati; Boni Saputra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This study aims to evaluate the effectiveness of public policies in the Indonesian education sector through a literature study approach. The main focus is directed at three strategic government programs, namely the Smart Indonesia Program (PIP), the Smart Indonesia Card (KIP) for College, and the School Operational Assistance (BOS). These three programs have shown contributions in expanding access to education for underprivileged groups, but still face a number of challenges in their implementation. Common problems identified include inaccurate targeting of recipients, delays in disbursement of funds, weak supervision, and limited managerial capacity at the school and campus levels. This study synthesizes various study results to identify patterns of success and failure in program implementation, and offers recommendations for strengthening data-based policies and public participation. The results of the study indicate that program effectiveness is greatly influenced by the integration of data collection systems, the quality of financial management, and the availability of a comprehensive mentoring system. To achieve national education goals in a sustainable manner, a more adaptive, transparent, and inclusive policy reformulation is needed. Long-term evaluation and based on outcome indicators are crucial in ensuring program accountability and supporting fair access to education throughout Indonesia.